A comparison between tourists' profiles in two Italian wine routes - Galletto, Luigi (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2018)
The study presents a comparative analysis of the wine tourism demand characteristics on two Italian wine routes. The research focuses on the more significant aspects that contradistinguish the wine tourists who frequent the Piave Wine Road and the Soave Wine Road, relying on 576 tourists' interviews. Through logistic regression, the identified variables may increase the relative propensity for a wine tourist to choose one or other itinerary. The results confirm a rather significant diversity between the two profiles (84% of cases are correctly classified). They show that the aspects that imply a greater propensity to travel along the Piave Wine Road rather than the Soave one correspond to an elderly foreign, university graduate tourist who have travelled for more than 3 days. This tourist pursues cultural activities, visits friends or acquaintances and tours with them. On the contrary, the latter one is more often preferred by someone aged less than thirty, who has learned of the route on a tourist board. He is less inclined to buy local wines and he spends less than 20 euro per meal. In this road is much more common the tendency to consider the wine tourism experience complete. Understanding the aspects that distinguish own wine tourists from other routes tourists allows Road Associations to position themselves better in an increasingly competitive market, in order to prepare appropriate territorial marketing strategies in relation to the wine tourism target that they intend to reach.